DROP OUT PENGOBATAN HIV PADA IBU BERDASARKAN AKSES LAYANAN PENGOBATAN DI KABUPATEN BANYUMAS TAHUN 2016 - Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Long-term treatment is common in every chronic disease, including HIV-AIDS, treatment includes administration of antiretroviral (ARV) drugs, prophylaxis, or treatment for opportunistic infections. Therapy compliance is the most important thing in replacing HIV replication and must be rejected. Constraints that occur to start ARV therapy are still often found by patients who already know their positive status but have not conducted CD4 and VL examinations for various reasons such as costs, distance from home and that are needed to compile consuls. HIV treatment for mothers who are completing a Drop Out of HIV Treatment in Banyumas District in 2016. The method of Qualitative research with case study design. The Informants selection of in this study was conducted by using non-probability sampling technique, how to collect the data in-depth interview method (indepth interview). the mainÂ  Informants are mothers who are dropped out in HIV treatment as much as 5 people. The secondary informants are husband/family and health workers. The results showed that of the 5 informants, 3 took medication at RSMS, 1 took at the cilongok I health center and 1 person took medicine at Baturaden II Health Center. The ease for HIV sufferers who cannot afford to receive KBS (Healthy Banyumas Card) by directly giving access to the Health Office without going through the procedure level to facilitate the confidentiality of the status of the mother and minimize the exchange that is done. Keywords: Drop out, HIV treatment, mother, access to treatment services